2015
DOI: 10.1002/clc.22362
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C–based CKD‐EPI Equations and N‐Terminal Pro‐B‐Type Natriuretic Peptide for Predicting Outcomes in Acutely Decompensated Heart Failure

Abstract: Background: In patients with acute decompensated heart failure (ADHF), both natriuretic peptides and renal impairment predict adverse outcomes. Our aim was to evaluate the complementary prognosis role of N-terminal pro-B-type natriuretic peptide (NT-proBNP) and the newly developed Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations based on cystatin C (CysC) for glomerular filtration rate (GFR) estimation in ADHF patients. Hypothesis: Renal impairment assessed by CysC-based CKD-EPI equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Instead, CKD-EPI SCR formula based on serum creatinine, which is widely used in clinical practice and has high international recognition. CKD-EPI is closer to the accurate value compared with the previous MDRD algorithm (31).…”
Section: Study Limitationsmentioning
confidence: 79%
“…Instead, CKD-EPI SCR formula based on serum creatinine, which is widely used in clinical practice and has high international recognition. CKD-EPI is closer to the accurate value compared with the previous MDRD algorithm (31).…”
Section: Study Limitationsmentioning
confidence: 79%
“…Our group has previously demonstrated that both CysC-based CKD-EPI equations outperformed the MDRD equation and added complementary information to natriuretic peptides for predicting adverse outcomes in acute HF patients. 34,35 In patients with acute myocardial infarction, Abu-Assi et al 36 reported that both CysC-based CKD-EPI equations were the most accurate for predicting in-hospital mortality, rather than the MDRD and CKD-EPI SCr equations. Almeida et al 37 found that the CKD-EPI CysC equation revealed the highest discriminative performance in predicting long-term mortality in patients with ACS and added predictive value to the GRACE risk score.…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason for this finding may be that our hospital is a tertiary referral centre for heart transplant candidates, and younger patients with a worse clinical condition are mostly referred to our centre for advanced therapies. When we looked at similar studies evaluating mortality differences in ADHF patients, they principally included older subjects (60 years or more), 11,23,24 with an absence of younger patients, which might have limited data on differences in mortality rates in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a previous report, a combination of cystatin C and NT-proBNP level was used as a predictor of unfavourable results in subjects with acute decompensated HF (ADHF). 11 The authors reported that combination of the two parameters was useful in predicting patients who had the highest risk for worse outcomes. However, in the literature, there are no data about the relationship between hospital admission cystatin C levels and mortality on an annual basis.…”
mentioning
confidence: 99%